Investigating how different information channels together affect drivers’ trust in automated vehicles - Fenelius, Jonathan; Wahlund, Jonathan (My University, 2021)
The transition towards automated vehicles (AV) is in full motion. When the level of automation increases, cars take over more and more driving tasks. This makes trust a fundamental factor for users to accept and adopt the technology. For users to reap the benefits when using AVs, it is important that users develop an appropriate level of trust (Lee & See, 2004). This project aims to aid users in developing an appropriate level of trust towards AVs by studying how different information channels, such as display, speakers, and driving behaviour, together interact in an information gestalt when forming users’ trust. This was studied by identifying the most prominent information channels. The display was shown to be the most prominent information channel when it comes to conveying detailed information and developing an understanding and consequently trust for the AV. Speaker emerged as an information channel that prepared the user, guided the attention to the display and confirmed the information in the display. Driving behaviour was also shown to be important when building trust towards AVs. To test how the information channels interact when forming trust, three different design concepts, each including a visual interface with matching sounds were designed. Different combinations of the designed display and the speaker information channels were tested in a simulator study (Study 2) and an online study (Study 3). These studies showed that information channels do interact and form an information gestalt and that this can result in increased trust. The results showed that there seems to be an increase in trust towards the AV and an increased sense of safety when users are presented with information from the combination of the display and the speaker information channels compared to being presented with the individual information channels, separately. Different interaction effects between the display and speakers, which could only be seen when the combination of the display and speakers were presented, was also identified. These were: • Audio information guides the attention to the display. • Audio information confirms the information in the display. • The display information channel helps users to understand the audio information. • Audio information could be played before the car takes action to prepare the user and reduce motion sickness. Further, 3 design factors that affect users’ trust towards AVs have also been identified for the visual and audio information presented through the display and speaker information channels. These are: • A serious-looking display interface and conventional sounds that the users are familiar with has been shown to increase trust. • A playful interface will not be taken seriously when it comes to traffic safety. • Showing a realistic representation of reality in the display will increase the understanding and consequently the trust towards the AV. These findings, and many more, were summarised in a list of guidelines to aid designers when designing for an appropriate level of trust in AVs.